Anisotropy of subsoil pore characteristics and hydraulic conductivity as affected by compaction and cover crop treatments. Issue 1 (24th February 2021) - Pulido‐Moncada, Mansonia; Labouriau, Rodrigo; Kesser, Merek; Zanini, Pedro Paulo Gonçalves; Guimarães, Rachel Muylaert Locks; Munkholm, Lars J.
Abstract: The natural and cover crop (CC)‐induced anisotropy of subsoil pore characteristics is important in assessments of soil compaction but, until recently, has received limited attention. This study aims to quantify the anisotropy of soil pore characteristics and hydraulic conductivity in subsoils subjected to compaction and CC treatments in a split‐plot field experiment on temperate sandy loam soils. The main factor was ±compaction and the split‐plot factor was ±CC with fodder radish ( Raphanus sativus L.). The compacted plots were heavily trafficked for 4 yr (2010–2013). After 4 yr under CC (2013–2016), core samples were collected at 0.3 m. The samples were taken vertically and horizontally to quantify the anisotropy of air‐filled porosity ( ε a ) and air permeability ( k a ), saturated hydraulic conductivity ( k sat ), and bulk density (ρb ). The results showed isotropic behavior for ρb and εa and significant anisotropic behavior ( p < .05) for k a, pore geometry index (PO1) ( k a / ε a ), ratio of non‐Darcian to Darcian k a ( R ‐ratio), and k sat . For parameters with significant anisotropy, higher values occurred vertically than horizontally for all compaction –CC combinations, except for R ‐ratio. This indicates that pre‐existing vertical continuous pores dominated the pore system in the control subsoil. A nonsignificant trend of higher values of k a, PO1, and k sat in the +CC than in the compacted –CC plots suggest that CC could contribute to the formation of vertical biopores. Including an autumn CC in rotation with a summer cereal crop for a longer period may significantly affect the anisotropy of the soil pore and hydraulic properties. Core Ideas: The preferentially vertical dynamic soil properties were independent of compaction. Tubular continuous vertical pores dominated the pore system in agricultural subsoil. The cover crop slightly improved soil gas and water transport in compacted subsoils.